2001
DOI: 10.31899/rh4.1159
|View full text |Cite
|
Sign up to set email alerts
|

Expansion of postpartum/postabortion contraception in Honduras

Abstract: In Honduras, 54 percent of deliveries are assisted by medical staff and 39 percent of deliveries take place at Ministry of Health of Honduras (MOH) health centers or hospitals. Although the unmet need for family planning services is relatively high (11% of women) and family planning helps protect mothers' and children's health, hospitals in Honduras rarely offer postpartum/postabortion contraceptive services.Between 1996 and 1999, the Ministry of Health and the Population Council's INOPAL III Project tested th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 1 publication
0
22
0
Order By: Relevance
“…In five countries in Latin America and the Caribbean, about half of pregnant women receive some family planning information during antenatal care visits. Likewise, the proportion of women who receive information on danger signs and symptoms, breastfeeding, immunizations, and other important information for preserving their own and their children's health varies widely within sub-Saharan Africa and Latin America and the Caribbean, but never approaches 100 percent (Medina et al 2001;Brambila et al 2002;Jacobs et al 2002;Rivero-Fuentes et al 2007;Solís et al 2007).…”
Section: Counseling and Information During Antenatal Carementioning
confidence: 99%
See 4 more Smart Citations
“…In five countries in Latin America and the Caribbean, about half of pregnant women receive some family planning information during antenatal care visits. Likewise, the proportion of women who receive information on danger signs and symptoms, breastfeeding, immunizations, and other important information for preserving their own and their children's health varies widely within sub-Saharan Africa and Latin America and the Caribbean, but never approaches 100 percent (Medina et al 2001;Brambila et al 2002;Jacobs et al 2002;Rivero-Fuentes et al 2007;Solís et al 2007).…”
Section: Counseling and Information During Antenatal Carementioning
confidence: 99%
“…Thus, to increase the proportion of fully informed clients, programs may need to offer information, counseling, and services at all contact points between clients and the maternal health-care system through the complete maternal cycle. This practice would also be aligned with women's preferences: surveys in health-service-delivery outlets around the world have shown that of the women who wish to start using a contraceptive method in the first year after delivery, more than half would prefer to begin using it immediately after delivery or at six weeks; the rest would prefer to begin use between six weeks and one year after delivery, most often at six months or when menses returns Medina et al 2001;Quiterio et al 2007;Rivero-Fuentes et al 2007;Solís et al 2007;Warren et al 2008a and.…”
Section: Counseling and Information During Antenatal Carementioning
confidence: 99%
See 3 more Smart Citations